Fourteen new generic and ten new specific synonymies in Pholcidae (Araneae), and transfer of Mystes Bristowe to Filistatidae - Huber, Bernhard A.; Colmenares, Pío A.; Ramirez, Martin J. (Zootaxa, 2014)
Between 1998 and 2011, the Venezuelan arachnologist Manuel Ángel González-Sponga (GS) published a series of taxonomic papers devoted to the Pholcidae of Venezuela. Of his 22 new genera, 20 were monotypic when described, suggesting a high percentage of synonyms. We studied his descriptions and as far as accessible his type specimens and propose the following new generic synonymies: Autana GS, 2011 = Mesabolivar GS, 1998; Ayomania GS, 2005 and Venezuela Koçak & Kemal, 2008 (new replacement names for Falconia GS, 2003) = Mecolaesthus Simon, 1893; Carbonaria GS, 2009 = Mecolaesthus Simon, 1893; Caruaya GS, 2011 = Mesabolivar GS, 1998; Coroia GS, 2005 = Artema Walckenaer, 1837; Maimire GS, 2009 = Mecolaesthus Simon, 1893; Moraia GS, 2011 = Mecolaesthus Simon, 1893; Nasuta GS, 2009 = Mecolaesthus Simon, 1893; Portena GS, 2011 = Metagonia Simon, 1893; Rioparaguanus GS, 2005 = Mesabolivar GS, 1998; Tonoro GS, 2009 = Litoporus Simon, 1893; Sanluisi GS, 2003 = Mecolaesthus Simon, 1893. Three of the type species are also specific synonyms: Autana autanensis GS, 2011 = Mesabolivar aurantiacus (Mello-Leitão, 1930); Coroia magna GS, 2005 = Artema atlanta Walckenaer, 1837; Tonoro multispinae GS, 2009 = Litoporus uncatus (Simon, 1893). Six species that González-Sponga described under Blechroscelis (a genus previously synonymized with Priscula Simon, 1893) are all synonyms of Mesabolivar eberhardi Huber, 2000 (B. acuoso GS, 2011; B. araguanus GS, 2011; B. blechroscelis GS, 2011; B. copeyensis GS, 2011; B. cordillerano GS, 2011; B. andinensis GS, 2011). In addition, and unrelated to González-Sponga’s work, we synonymize the Central Asian monotypic genus Ceratopholcus Spassky, 1934 with Crossopriza Simon, 1893; we synonymize the Chinese species Pholcus acerosus Peng & Zhang, 2011 with Pholcus fragillimus Strand, 1907 and remove the Malaysian monotypic genus Mystes Bristowe, 1938, previously thought to be the only East Asian representative of the subfamily Ninetinae, to the family Filistatidae.